Characterisation of soil organic matter in the topsoils under rain forest and pastures in the eastern Brazilian Amazon Basin - Koutika, L.; Andreux, F.; Hassink, J.; Chone, T.; Cerri, C.C. (1999)
In topsoils under forest and 7-, 12- and 17-year-old pastures, organic matter was characterized by analysing C and N distribution in particle-size fractions, the C decomposition rates of soil and particle-size fractions and by employing density-fractionation of macro-organic matter (>150 μm). The C and N associated with clay fractions increased with increasing age of pasture. The weight (%) of macro-organic matter and its heavy fractions (>1.37 g cm–3) also increased with increasing age of pasture. However, in a long-term incubation (100 days), these changes seemed to involve an increase in the C decomposition rate in the topsoil of the oldest pasture. Using the C decomposition rates of particle-size fractions, it appeared that silt and clay contributed differently to C decomposition in the whole soil. C associated with silt contributed to the C decomposition rate during the first 40 days of incubation, while C associated with clay contributed to C decomposition in the long-term incubation (after 40 days), especially when the clay fraction appeared to reach saturation point with respect to its ability to bind organic compounds and thus protect the soil from C loss.